2020
DOI: 10.1101/2020.08.25.267419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal changes in brain metabolites in healthy subjects and patients with first episode psychosis (FEP): a 7-Tesla MRS study

Abstract: OBJECTIVE: 7 Tesla (T) longitudinal magnetic resonance spectroscopy (MRS) offers a precise measurment of metabolic levels in human brain via a non-invasive approach. Studying longitudinal changes in neurometabolites could help identify trait and state markers for diseases and understand inconsistent findings from different researchers due to differences in the age of study participants and duration of illness. This study is the first to report novel longitudinal patterns in young adulthood from both physiologi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Under such premise, we used classification models with trait markers to evaluate the performance of individual markers as well as the combination of them. Our previous longitudinal assessment for the same cohort used in the present study showed that the ACC-GSH levels were stable in patients between 15-35 years of age [52]. Using the same analytic pipeline that we used to assess longitudinal changes in the ACC-GSH level [52], we found that the right HP volume and the left SFG volume were also stable in FEP patients ( Table S6 : see also details in the supplementary methods).…”
Section: Resultssupporting
confidence: 58%
“…Under such premise, we used classification models with trait markers to evaluate the performance of individual markers as well as the combination of them. Our previous longitudinal assessment for the same cohort used in the present study showed that the ACC-GSH levels were stable in patients between 15-35 years of age [52]. Using the same analytic pipeline that we used to assess longitudinal changes in the ACC-GSH level [52], we found that the right HP volume and the left SFG volume were also stable in FEP patients ( Table S6 : see also details in the supplementary methods).…”
Section: Resultssupporting
confidence: 58%
“…The same stability in GSH levels was also seen in the 10 demographically healthy controls scanned at 2 time points (Mean(SD) at baseline =1.64 (0.25), at 6-months = 1.63 (0.32)) [84]. In a larger sample of 38 patients with first episode psychosis (onset within 2 years) and 48 healthy controls followed up over 4 years [85], GSH levels was found to have a near zero change in all 5 studied brain regions (ACC, thalamus, DLPFC, centrum semiovale and orbitofrontal cortex) over time, strongly arguing for a 'trait-like' stability of GSH levels compared to other metabolites. These observations do not rule out within-individual differences over time, and the possibility of an early excess in untreated state; but provide a strong support for the presence of a distinct subgroup with GSH-deficit that is over-represented in more established phase of schizophrenia, in association with reduced treatment responsiveness and poor functional outcomes.…”
Section: Intracortical Gsh In Schizophrenia: Mrs Studiesmentioning
confidence: 52%
“…Support for this explanation comes from the existing longitudinal studies of ACC GSH in schizophrenia which do not reveal a picture of dynamic change in GSH levels. Instead, existing longitudinal MRS (44,45) as well as genetic studies (31) indicate a constitutional deficit of GSH, at least in some individuals with schizophrenia. The modest effect-size of the reported GSH deficit even in the chronic and partially treatment-resistant samples (7,46), suggests that either (1) only a small number of patients belong to the putative FIGURE 2 | (A) In this model, a primary defect in glutathione generation is thought to contribute to NMDA hypofunction in cortical microcircuits, leading to relative glutamatergic excess via disinhibition of pyramidal neurons.…”
Section: Discussionmentioning
confidence: 99%